1994
DOI: 10.3171/jns.1994.81.3.0466
|View full text |Cite
|
Sign up to set email alerts
|

Malignant meningioma in Gorlin's syndrome: cytogenetic and p53 gene analysis

Abstract: Gorlin's syndrome, also known as multiple basal cell carcinoma syndrome, is a familial tumor condition with autosomal-dominant inheritance. Patients develop multiple basal cell carcinomas beginning in childhood. They also have a typical dysmorphic facies, skeletal malformations, and a particular type of epithelial cyst of the jaws. Recent evidence localizes a Gorlin's syndrome locus on chromosome 9 at band q31. Both tumors and malformations of the central nervous system occur with Gorlin's syndrome. Medullobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
2
20
1
1
Order By: Relevance
“…Nevoid basal cell carcinoma syndrome associated with both medulloblastoma and meningioma has been reported in only two patients, in whom the meningioma was probably induced by the radiation. 1,12) In our case, there was no clear evidence that the meningioma occurred following irradiation of the medulloblastoma or any association with nevoid basal cell carcinoma syndrome. However, meningioma is known to occur within the irradiated field for medulloblastoma.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Nevoid basal cell carcinoma syndrome associated with both medulloblastoma and meningioma has been reported in only two patients, in whom the meningioma was probably induced by the radiation. 1,12) In our case, there was no clear evidence that the meningioma occurred following irradiation of the medulloblastoma or any association with nevoid basal cell carcinoma syndrome. However, meningioma is known to occur within the irradiated field for medulloblastoma.…”
Section: Discussioncontrasting
confidence: 63%
“…Nevoid basal cell carcinoma syndrome is an autosomal dominant disorder linked to chromosome 9q22.3-q31 (40% of new cases are sporadic) 1,12) and may be related to PTCHgene. 3,9) More than 30 different malformations and benign or malignant tumors have been associated with this syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small number of case reports and only two series have demonstrated this relation with respect to syndromes other than NF1. 3,13,[22][23][24] Kingston et al reported that a genetic condition other than NF1 was present in 5 of 45 children (11%) with primary CNS tumors who later experienced an SN; 3 of those patients had Gorlin syndrome, 1 patient had Turcot syndrome, and 1 patient had tuberous sclerosis. 3 In the other series, two patients with Gorlin syndrome were among the four patients overall who developed an SN.…”
Section: Discussionmentioning
confidence: 99%